MEDIA PEMBELAJARAN GAME QUIZ EDUKASI DI ERA DIGITAL UNTUK MENINGKATKAN PRESTASI SISWA - Awalia, Rubi; Mustofa, Ali; Lailiyah, Nurul (ILJ: Islamic Learning Journal, 2024)
In today's digital era, the development of information technology, especially in Indonesia, is increasingly advanced, with this education must also be able to compete with these developments with innovations from educators, in order to compete with the development of learning media in various countries that have advanced their education systems. This research is literature, with the method of collecting data documentation and analysis using content analysis. The results of the study state that quizizz as one of the game-based learning media has a good impact on students. Learning becomes fun and not boring because students feel like they are playing a game, sharpening students' competitive spirit because quizizz shows directly the score that students get each time they answer a question, increasing focus in learning, being more enthusiastic, and stimulating students to understand questions better than textbook-based questions.